Analysis of Factors Influencing Health Personnel Implementing Hand Hygiene at Peulumat Health Center, South Aceh - Hendraliyusman Hendraliyusman; Nuraini Nuraini; Mufli Mufli (PROMOTOR, 2024)
Compliance with health workers in implementing hand hygiene is critical because non-compliance can cause infection and disease transmission. This study aims to analyze the factors that influence the influence of health workers on hand hygiene at the Peulumat Health Center, South Aceh. The research method used was descriptive correlation with a cross-sectional approach, involving 80 health workers as samples. Data was obtained through interviews using a questionnaire. The results of statistical analysis show that attitude (p 0.003), length of service (p 0.002), and availability of hand hygiene facilities (p 0.000) influence the compliance of health workers at the Peulumat Health Center in South Aceh. The implication is that there is a need to increase supervision and motivation of health workers according to recommendations, and further research with a larger sample, involving other researchers, and using video media is recommended.